Yacon root is a functional food beneficial for human health: a meta-analysis of clinical trials - Pan, Ling-Hui; Yao, Zhong-Wei; Hu, Wei-Feng; Jia, Hui-Tian; Ren, Wen-Lu; Wang, Pan-Pan; Ling, Su-ping; Zhu, He (Frontiers in Nutrition, 2025)
Yacon (Smallanthus sonchifolius) is a perennial herbaceous plant in the Asteraceae family, native to the Andean region of South America. Yacon root (YR) is considered to be a functional food but with inconsistent conclusions. We hypothesized that YR beneficially modulates human health. This study aims to evaluate the effects of YR on human health through clinical trials to determine whether YR can be classified as a functional food. We systematically searched PubMed, Cochrane Library, Springer, and Web of Science for clinical outcomes related to YR from 2000 to 2025. The health benefits of YR were evaluated through a meta-analysis. Twelve studies were included in the analysis. The pooled results showed that YR significantly reduced BMI [SMD = −0.81, 95%CI (−1.54, −0.08)], decreased stool pH [SMD = −1.12, 95%CI (−1.61, −0.62)], softened stools [SMD = 0.94, 95%CI (0.08, 1.80)], facilitated defecation [SMD = 4.03, 95% CI (0.54, 7.52)], improved fiber consumption patterns [SMD = 0.58, 95%CI (0.18, −0.99)]. Additionally, YR tends to reduce body weight, waist circumference, postprandial blood glucose and triglyceride levels, and dietary intake of energy, carbohydrates, fats, and proteins. Collectively, YR shows evidence supporting its classification as a functional food for weight control, constipation relief. These effects may be ascribed to active components, such as inulin-type fructans and phenolic compounds. However, the limited quality of the included studies indicates that future high-quality clinical trials are necessary to confirm YR’s effectiveness.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024606929, identifier (CRD42024606929).